Squamous Cell Carcinoma of the Conjunctiva (Scc) and Human Immunodefisciency Virus (Hiv): What Reality in Ivory Coast Through 23 Cases? - Coulibaly R Berete; Abokan J Konan; Thierry Y C Sowagnon; Kouassi S Kouakou; Adama Fanny (Journal of Clinical Research In HIV AIDS And Prevention, 2017)
Introduction: Squamous cell carcinomas of the conjunctiva (SCC) are rare neoplasia but have a high rate of increase and a high rate of mortality, especially when they occur in the context of Human Immunodeficiency Virus (HIV) infection. The objective of this study was to establish an epidemiological and clinical profile of SCC in patients living with HIV and to assess its evolutionary characteristics. Patients and Methods: this was a descriptive cross-sectional study carried out over a period of 5 years in the ophthalmology department of the University Hospital of Treichville. The data collected focused on epidemiological, clinical, pathological, therapeutic and evolutionary elements. Twenty tree eyes of 23 patients were examined during this period. Results: The average age of our patients was 45 years with extremes ranging from 31 to 60 years. A female predominance was observed with a sex ratio of 0.92. The average consultation period was 18 months with extremes ranging from 6 to 60 months. Physically, 35% of our eyes (08 eyes) presented a functional loss of the eye. All our patients had a HIV positive status with 16 cases of HIV1 infection, 4 cases of HIV 2 infection and 3 cases of HIV 1 and 2 co-infection. Lymphocyte typing was performed for 15 patients out of the 23 With CD4 cell counts ˂ 200 in 30.43% of cases, between 200 and 500 in 34.78% of cases. All our tumors had had biopsy excision with pathological examination. A postoperative adjuvant topical chemotherapy in 6 cases. The average follow-up period of our patients was 29 months. In all cases, it was invasive differentiated squamous cell carcinoma. Discussion: HIV infection is a risk factor for the occurrence of conjunctival squamous cell carcinoma, but it is also an aggravating factor especially in the case of low CD4 cell count, particularly in sub-Saharan Africa, where the fight against infection, although boosted in these recent years, is far to achieve all objectives Conclusion: HIV seroprevalence is very often associated with opportunistic infections which include carcinogenic processes such as squamous cell carcinomas of the conjunctiva
Keywords: squamous cell